Comparison of Cephalothin and Cefamandole Prophylaxis During Insertion of Prosthetic Heart Valves - Archer, Gordon L. (1978)
Cefamandole nafate (CM) and cephalothin sodium (CP) were administered as prophylaxis in a randomized, prospective study to 30 consecutive patients undergoing prosthetic cardiac valve insertion. A single dose of 20 mg/kg was given intramuscularly during anesthesia induction, and serial plasma antibiotic concentrations, atrial muscle and cardiac valve tissue antibiotic levels, plasma bactericidal activity against pathogenic staphylococci, and infectious complications were determined and compared for the two drugs. Both antibiotics produced high plasma levels (>20 μg/ml 30 min after injection) which fell less than 25% during the period of cardiopulmonary bypass. However, CM levels were significantly higher at most time periods (P<0.05) than CP levels. CP levels were undetectable in atrial muscle from 14 of 15 patients and in valves from 10 of 15 patients. In contrast, CM bioactivity was found in all tissues. Differences in tissue antibiotic concentration could not be accounted for by differences in plasma concentrations or by CP tissue binding and were assumed to be caused by differences in penetration. Plasma bactericidal activity against staphylococci was equal for the two drugs (median titer, 1:16). No infections were seen in either group. CM appeared to be an effective and perhaps preferable prophylactic antibiotic for use during cardiac surgery.